Implementasi Kebijakan Layak Anak Dalam Program Sekolah Ramah Anak (SRA) di SD Negeri Kedondong Kecamatan Sokaraja - Alifiani, Respa Nur; Sutikno, Chamid; Pribadi, Indah Ayu Permana; Amanda, Ariesta; Milatta, Chanifia Izza (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
Implementation of educational policies made by the government as a reaction to the emergence of various educational problems that have become public attention and as a guide for action in managing education. One of them is by establishing a Child-Friendly School Program (SRA) policy to support Child-Friendly Districts (KLA), where in 2023 Banyumas district will still get a pratama (lowest predicate) because not all educational institutions in Banyumas district have implemented child-friendly policies, especially in child friendly school program. Kedondong State Elementary School is one of the elementary schools that has implemented a child-friendly school program and has won national championships. This problem drives the aim of this research to examine the process of implementing child-friendly district policies in the Child-Friendly School Program (SRA) at Kedondong State Elementary School. This research uses qualitative research methods by collecting data through observation, interviews and documentation by determining informants using snowball sampling and purposive sampling. The results of the research show that Kedondong State Elementary School is one of the schools in Banyumas district that has successfully implemented the Child Friendly School Program (SRA) by winning second place in the child friendly school competition focused on school safe snack food (PJAS) activities.